Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis: A case report. Issue 17 (30th April 2021) - Yang, Jing; Du, Jichen; Zhao, Jing; Liu, Haichao; Zhang, Lvming; Cai, Lina; Wang, Qi; Han, Bailin; Cui, Jiangbo
Abstract: Introduction: : Anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) is a subtype of glutamate receptor that mediates most of the fast excitatory neurotransmission in the brain. Anti-AMPAR encephalitis is an autoimmune-mediated neurological disorder, frequently accompanied by the presence of neoplasms, comprising a spectrum of paraneoplastic syndrome. Patient concerns: A 56-year-old man was admitted for deterioration in memory and aberrant psychological behaviors, which lasted for at least 20 days Diagnosis: The patient was diagnosed as anti-AMPAR encephalitis and 4 months later, he was diagnosed with small cell lung cancer. Interventions: Once diagnosis for anti-AMPAR encephalitis was confirmed, methylprednisolone was prescribed with initial dose 500 mg/d for 14 days until the patient returned to pre-illness state. Then he was discharged with oral treatment with corticosteroids. Following the diagnosis of small cell lung cancer, he received 5 rounds of chemotherapy, including carboplatin and etoposide. Outcomes: After taken the prescription of Methylprednisolone for anti-AMPAR encephalitis, he returned to pre-illness state and was discharged. In April 21, 2017, after symptoms of respiratory system showed up, he was diagnosed with small cell lung cancer and he eventually died of respiratory failure. Conclusion: Though progress has been made in recent years in diagnosis and treatment for autoimmune encephalitis, it is challenging to diagnose due to the similarity in clinical findings with other autoimmune or infectious encephalitis. In addition, it is necessary for these patients to regularly have tumor screening, considering AMPAR antibody encephalitis is closely associated with neoplasm, and the incidence of paraneoplastic syndrome is 63% to 70%.